COVID-19 in people living with HIV: A multicenter case-series study - Alfonso Cabello; Belén Zamarro; Sara Nistal; Virginia Víctor; Jana Hernández; Laura Prieto-Pérez; Irene Carrillo; Beatriz Álvarez; R. Fernández‐Roblas; Marta Hernández-Segurado; Javier Becares; José M. Benito; et al. (2020)
ObjectivesInformation on how COVID-19 affects people living with HIV (PLHIV) remains scarce.MethodsAn observational study was conducted in four public hospitals in Madrid. All HIV patients with confirmed or suspected COVID-19 were included and compared with COVID-19 patients without HIV infection.ResultsSixty-three patients with HIV infection and confirmed or suspected COVID-19 were analyzed. The median age was 46 years (IQR: 37–56 years), and 88.9% were men. The median duration of HIV infection was 10.8 years (IQR: 6.5–16.8 years), and 96.8% were on antiretroviral therapy. 84.1% had previous comorbidities. The most common symptoms were fever (66.1%), cough (66.1%) and dyspnea (46.8%). Pneumonia was found in 47.5%, 28.6% of patients had severe disease, and 32.3% were admitted to hospital. The ICU admission rate and the mortality rate were both 3.17%. A significant association was observed between age, arterial hypertension, overweight, and diabetes mellitus and the severity of COVID-19. No association was observed between HIV-related factors and the severity of COVID-19. The rate of COVID-19 in HIV-patients was 1.68%. Similar hospitalization (31.74% vs 32.57%) and ICU admission (3.17% vs 2%) rates were observed with non-HIV infected patients. A lower mortality rate during hospitalization (10% vs 21.37%) and a lower global mortality rate (3.17% vs 6.96%) were also observed.ConclusionsEstablished poor prognostic factors for COVID-19 patients, such as age and comorbidities, remain the main determinants for PLHIV. Neither the HIV severity nor the type of ARV treatment seem to influence the outcome of COVID-19. Large prospective cohorts are needed in order to establish the differences between HIV-positive and HIV-negative patients.